The m6A methyltransferase METTL16 inhibits the proliferation of pancreatic adenocarcinoma cancer cells via the p21 signaling pathway - Xie, Fuming; Zheng, Yao; Fu, Wen; Chi, Bojing; Wang, Xianxing; Zhang, Junfeng; Gu, Jianyou; Yin, Jingyang; Zhou, Qiang; Guo, Shixiang; Cai, Lei; Yang, Jiali; et al. (Frontiers in Oncology, 2023)
Background: Many studies have reported that N6-methyladenosine (m6A) modification plays a critical role in the epigenetic regulation of organisms and especially in the pathogenesis of malignant diseases. However, m6A research has mainly focused on methyltransferase activity mediated by METTL3, and few studies have focused on METTL16. The aim of this study was to investigate the mechanism of METTL16, which mediates m6A modification, and its role in pancreatic adenocarcinoma (PDAC) cell proliferation. Methods: Clinicopathologic and survival data were retrospectively collected from 175 PDAC patients from multiple clinical centers. METTL16 and CCK8 expression was detected and cell cycle, EdU, and xenograft mouse model experiments were used to evaluate the proliferation effect of METTL16. Potential downstream pathways and mechanisms were explored via RNA sequencing, m6A sequencing, and bioinformatic analyses. Regulatory mechanisms were studied through methyltransferase inhibition, RT‒qPCR, and Western blotting assays. Results: We found that METTL16 expression was markedly downregulated in PDAC, and multivariate Cox regression analyses revealed that METTL16 was a protective factor for PDAC patients. We also demonstrated that METTL16 overexpression inhibited PDAC cell proliferation. Furthermore, we identified a METTL16-p21 signaling axis, with downregulation of METTL16 resulting in inhibition of p21. Additionally, METTL16 silencing and overexpression experiments highlighted m6A modification alterations in PDAC. Conclusions: METTL16 plays a tumor-suppressive role and suppresses PDAC cell proliferation through the p21 pathway by mediating m6A modification. METTL16 may be a novel marker of PDAC carcinogenesis and target for the treatment of PDAC.